Critical aspects of gender in conflict resolution, peacebuilding, and social movements - Snyder, Anna C.; Stobbe, Stephanie P. (Research in social movements, conflicts, and change, 2011)
This volume of Research in Social Movements, Conflicts and Change explores the important dimension of gender and how women are key contributors to conflict resolution, peace, and social movements throughout the world. Womens networks and their collective activism have increased social justice, peace, and reconciliation in communities. Grassroots initiatives from women groups have positively impacted relationships, peace processes, and peace treaties. The volume includes scholarly research that highlights womens activism in countries such as Sierra Leone, Liberia, El Salvador, Czech Republic, Uzbekistan, South Africa, and United States. Critical issues of poverty, violence, civil wars, inequality, sexual identity, and peace are examined from a gendered perspective.